Prospek Industri Asuransi di Indonesia - Heri Sasono; Paidi WS (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Theoretically, the relationship between insurance and economic growth can be a causal relationship, economic growth supports insurance growth or insurance growth supports economic growth. The aim of this research is to look at the prospects for insurance growth which are linked to macroeconomic indicators, such as: growth in the number of insurance companies, investment funds, gross premium receipts, economic growth and gross domestic product.The research method used is descriptive analysis which discusses insurance growth over the 10 (ten) years from 2013 to 2022. The research results show that, this can be seen from the average growth over the 10 (ten) years from 2013 to 2022, including; insurance company growth was 0.83%, investment fund growth was 11.48%, gross premium receipts growth was 12.80%, and average economic growth in Indonesia was 4.87% and gross domestic product growth was 8.41%.